An Evaluation of Implementation A Covid-19 Vacination Program in Hospital Royal Prima 2021 - Zsa Zsa Ranty Bianca Saragih; Ermi Girsang; Sri Lestari Nasution; Tan Suyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper describes a covid-19 pandemic that has put the entire world's population in a very worrying situation almost all countries in the world feel the impact. All countries in the world have implemented several policies to overcome the Covid-19 pandemic, including by enforcingLockdown, Large-Scale Social Restrictions (PSBB) and recently the government implemented PPKM to suppress the spread of Covid-19. However, it seems that it has not been successful enough, this can be seen from the number of positive cases of Covid-19 every day is still high. Seeing this problem, it is necessary to do a more effective and efficient way to deal with the ongoing Covid-19 pandemic. (WHO, 2021). Various methods have been taken by the government or the health Team to reduce the number of cases of Covid-19, but in reality, the number is still increasing. Seeing this problem, it is necessary to do a method or container that is more attractive and easier for the community to use to carry out the initial treatment if signs and symptoms of being infected with Covid-19 are found. One of the most effective ways is the provision of vaccines for every Indonesian citizen. (Covid & Team, 2020).